Social Relationship at Workplace and Emotional Attachment of Employees: An Evidence of Pokhara Based Development Bank - Adhikari, Nabin Bahadur (Janapriya Journal of Interdisciplinary Studies, 2018)
Effective social relationship at workplace and the emotional attachment is must for the survivable and betterment of the organization. This research paper aims to investigate employee social relationship at work and their emotional attachment with organization. For this regard hypothesis were set to test under some constraints. The study applied empirical approach in which a survey questionnaire was used to collect quantitative data and other statistical techniques like Chi square test, Pearson correlation was applied and conclude that employee commitment towards organization has some relationship to the social relationship at workplace. Additionally, the level of job involvement is associated with social relationship at workplace. Employee who is highly involved in job may not have the same proportion of level of social relationship at workplace. Janapriya Journal of Interdisciplinary Studies, Vol. 6 (December 2017), page: 88-96